Foreign bank entry and the outward foreign direct investment of companies: evidence from China - Liu, Haiyue; Yi, Zhimin; Shang, Hua; Liu, Zihan (Journal of International Business Studies, 2024)
Globalization is motivating many emerging market firms (EMFs) to expand operations through outward foreign direct investment (OFDI). General FDI theories, such as internalization theory and the OLI paradigm, are based on industrialized countries, leading to inevitable gaps in explaining the OFDI activities of EMFs. We extend the literature by establishing a connection between international finance and the internationalization of EMFs. We argue that foreign banks operating in emerging markets offer a diverse set of resources that can help EMFs expand globally. Under gradually easing foreign bank entry restrictions in China, utilizing a panel dataset of Chinese listed companies spanning 2001–2018, we find a positive association between foreign bank entry and the OFDI activities of Chinese companies. The identified channels include direct loan support from foreign banks, information support from foreign banks’ global branch networks, a high level of internationalization, and close proximity to local companies, as well as loan support from domestic banks under foreign bank competition. The entry of foreign banks particularly stimulates OFDI in non-state-owned, higher profitability companies, in medium-sized, low financial marketization, and node cities designated in the Belt and Road Initiative. These findings provide new insights into emerging market financial openness and the internationalization of EMFs.